Evidence of balanced diversity at the chicken interleukin 4 receptor alpha chain locus - O'FARRELLY, CLIONA; BRADLEY, DANIEL GERARD MARY; LLOYD, ANDREW THOMAS (My University, 2009)
BACKGROUND: The comparative analysis of genome sequences emerging for several avian species with the fully sequenced chicken genome enables the genome-wide investigation of selective processes in functionally important chicken genes. In particular, because of pathogenic challenges it is expected that genes involved in the chicken immune system are subject to particularly strong adaptive pressure. Signatures of selection detected by inter-species comparison may then be investigated at the population level in global chicken populations to highlight potentially relevant functional polymorphisms. RESULTS: Comparative evolutionary analysis of chicken (Gallus gallus) and zebra finch (Taeniopygia guttata) genes identified interleukin 4 receptor alpha-chain (IL-4Ralpha), a key cytokine receptor as a candidate with a significant excess of substitutions at nonsynonymous sites, suggestive of adaptive evolution. Resequencing and detailed population genetic analysis of this gene in diverse village chickens from Asia and Africa, commercial broilers, and in outgroup species red jungle fowl (JF), grey JF, Ceylon JF, green JF, grey francolin and bamboo partridge, suggested elevated and balanced diversity across all populations at this gene, acting to preserve different high-frequency alleles at two nonsynonymous sites. CONCLUSION: Haplotype networks indicate that red JF is the primary contributor of diversity at chicken IL-4Ralpha: the signature of variation observed here may be due to the effects of domestication, admixture and introgression, which produce high diversity. However, this gene is a key cytokine-binding receptor in the immune system, so balancing selection related to the host response to pathogens cannot be excluded.
PUBLISHED
Keywords: Genetics